Modern X-ray analysis on single crystals : a practical guide - Luger, Peter, 1943- (Walter de Gruyter GmbH & Co. KG, 2013)
This completely revised edition is a guide for practical work in X-ray analysis. Experimental developments e.g. brilliant X-ray sources, area detection, and developments in computer hardware and software have led to increasing applications in X-ray analysis. An introduction to basic crystallography moves quickly to a practical and experimental treatment of structure analysis. Essential reading from the student to the professional level.
Includes index.
Keywords: X-ray crystallography.; elektronické knihy; electronic books